Carbonation and Water Permeability of Foamed Concrete - Loon, Lee Yee; Ahmad Zaidi, Ahmad Mujahid; Boon, Koh Heng; Sulaiman, Suhaizad; Adnan, Suraya Hani; Rahman, Ismail (International Journal of Sustainable Construction Engineering and Technology, 2011)
This paper reports recent findings of a research programme focused on the carbonation and permeability of foamed concrete. The objective is to develop an environmentalfriendly and economical material for sustainable construction on peat. A four-year study showed that the rate of carbonation is related to the permeability, time and density. A water permeability test system has been developed based on ISO/DIS7031 and a draft standard prepared. They are aimed at promoting concrete durability research. It features a dual-test method for the measurement of water permeability with the standard 150 mm test cube prior to the determination of compressive strength. The calibration of the test system is by means of a mature test cube of known water permeability. The test system plays complementary role to the existing methods of assessing durability such as carbonation test and rapid chloride permeability. The test method is non-destructive, convenient and reliable for assessing concrete durability in the laboratory at the mix design stage. It can be used subsequently for tests on concrete products and structures for rain water harvesting system. Information technology has been experimented to provide online skill training and the electronic publications of research findings to promote good concrete practice via a concrete innovation blog http://www.1.net.my and a concreteresearch portal http://www.it-lodge.com.